The functional repertoire of survivin's tails - Wheatley, Sally P. (Taylor & Francis, 2015)
Survivin is a multitasking protein that can inhibit cell death and that is essential for mitosis. Due to these prosurvival activities and the correlation of its expression with tumour resistance to conventional cancer treatments, survivin has received much attention as a potential oncotherapeutic target. Nevertheless, many questions regarding its exact role at the molecular level remain to be elucidated. In this study we ask whether the extreme C- and NH2 termini of survivin are required for it to carry out its cytoprotective and mitotic duties. When assayed for their ability to act as a cytoprotectant, both survivin1-120 and survivin11-142 were able to protect cells against TRAIL-mediated apoptosis, but when challenged with irradiation cells expressing survivin11-142 had no survival advantage. During mitosis, however, removing the NH2 terminal 10 amino acids (survivin11-142) had no apparent effect but truncating 22 amino acids from the C-terminus (survivin1-120) prevented survivin from transferring to the midzone microtubules during anaphase. Collectively the data herein presented suggest that the C-terminus is required for cell division, and that the NH2 terminus is dispensable for apoptosis and mitosis but required for protection from irradiation.